Female association of seven species of the genus Amphinemura Ris, 1902 (Nemouridae: Amphinemurinae) in China based on morphological and molecular data - Wang, Bingli; Li, Xiaochen; Kong, Fanbin (Zootaxa, 2025)
Females of seven known species of nemourid stoneflies, Amphinemura claviloba (Wu, 1973), A. dabanshana Li, Du & Yang, 2017, A. hastata (Wu, 1973), A. multispina (Wu, 1973), A. ningxiana Li & Yang, 2011, A. pediformis Li & Yang, 2008 and A. qiliana Li, Teslenko & Yang, 2020, are described in this paper. DNA barcoding analysis confirmed the association between males and females, thus validating the morphological taxonomic conclusions.